The Effect of Service Quality to Improve Customer Retention Through Customer Satisfaction as a Mediation in Calibration Laboratory - Jamaluddin, M Nur; Hudayah, Syarifah; Indriastuti, Herning (LPPM of NAROTAMA UNIVERSITY, 2025)
This study aims to analyze the effect of service quality on customer satisfaction and retention at the UPTD Laboratory of BPSMB Samarinda. The approach used in this study is quantitative with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis method and involving 162 respondents as samples. Testing is carried out through evaluation of the outer model and inner model to assess the validity, reliability, and relationships between variables in the research model. The results of the analysis show that service quality has a direct and significant effect on customer satisfaction (coefficient = 0.812; t = 32.328; p <0.001), and has a direct effect on customer retention (coefficient = 0.408; t = 3.770; p <0.001). In addition, customer satisfaction also has a significant effect on customer retention (coefficient = 0.416; t = 3.723; p < 0.001) and partially mediates the relationship between service quality and customer retention (coefficient = 0.338; t = 3.638; p < 0.001). This finding confirms that customer satisfaction plays an important role as a mediator in shaping customer loyalty. Thus, consistently improving service quality is a key strategy in building satisfaction and maintaining customer loyalty.